Quantifying water use and nutritional water productivity of two sweet potato (Ipomoea batatasL.) cultivars grown in South Africa - Van der Laan, Michael (University of Pretoria, 2018)
Dissertation (MSc (Agric))--University of Pretoria, 2017.